2017
DOI: 10.1590/s1980-6574201700020006
|View full text |Cite
|
Sign up to set email alerts
|

Screen time between Portuguese and Brazilian children: a cross-cultural study

Abstract: -Aims:To verify differences in screen time (ST) (hours watching TV, using computer and/or video game) and to compare the percentage of meeting ST recommendation between Portuguese and Brazilian children. Methods: The sample comprised 369 children aged 9 year-old from Portugal (n=95) and Brazil (n=274). ST average (h/day), physical activity (PA) and socioeconomic status (SES) were estimated by parental-report questionnaire. The Student t test or the Mann-Whitney U test and binary logistic regression analysis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Children’s screen time also increases with age 11 , 13 , 15 18 with two-year-olds in the US having less than an hour of daily screen time and two- to four-year-olds having on average 2.5 h of daily screen time 13 . However, there appear to be differences in children’s screen time across countries 19 – 21 . For example, four to six-year-olds from medium–high SES families in Germany and Spain were reported to have 20–30 min of daily TV time, whereas this estimate was between 30–90 min in Greece, and 60–240 min in Belgium, Poland, and Bulgaria 20 .…”
Section: Factors Associated With Screen Time In Early Childhoodmentioning
confidence: 99%
“…Children’s screen time also increases with age 11 , 13 , 15 18 with two-year-olds in the US having less than an hour of daily screen time and two- to four-year-olds having on average 2.5 h of daily screen time 13 . However, there appear to be differences in children’s screen time across countries 19 – 21 . For example, four to six-year-olds from medium–high SES families in Germany and Spain were reported to have 20–30 min of daily TV time, whereas this estimate was between 30–90 min in Greece, and 60–240 min in Belgium, Poland, and Bulgaria 20 .…”
Section: Factors Associated With Screen Time In Early Childhoodmentioning
confidence: 99%
“…This value is double the sedentary time specified in international recommendations for this age group and contrasts with other investigations that observed a lower average screen time in samples of Brazilian, Portuguese, and North American children. 34,35 These data largely argue for policies to limit abusive screen use by children, because there is evidence of health harms in a wide range of health domains that go far beyond the oral aspects, but also the impact of this behavior on physical and biopsychosocial dimensions. 36 A recent systematic review investigated the content of television advertising during children's viewing time, focusing on the number of cariogenic food advertisements, and confirmed that the most frequently advertised foods during children's programming are foods that are potentially harmful to dental health, with a large amount of hidden sugars.…”
Section: Discussionmentioning
confidence: 99%
“…Although, in the current globalized society, unhealthy behaviours can be similar in different cultures. In this regard, cross‐cultural studies may be interesting to comprehend how dissimilar environments and different cultures may influence lifestyles 28 . Therefore, the cross‐cultural differences in lifestyle with regard to overweight and obesity are very relevant to scientists and governments, in most countries.…”
Section: Introductionmentioning
confidence: 99%